2023
DOI: 10.3389/fonc.2023.1086251
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between contrast-enhanced ultrasound and microvessel density in non-small cell lung cancer: A prospective study

Abstract: BackgroundImmunohistochemical microvessel density (MVD) is an early indicator of angiogenesis and it could be used to evaluate the therapeutic efficacy of non-small cell lung cancer (NSCLC). We sought to identify the ability of contrast-enhanced ultrasound (CEUS) in evaluating MVD of subpleural NSCLC.MethodsWe prospectively collected CEUS data of NSCLC confirmed by ultrasound-guided transthoracic needle biopsy from October 2019 to February 2021, The MVD of NSCLC counted by CD34-positive vessels of immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Contrast-enhanced ultrasound (CEUS) is widely used for ultrasound diagnosis of various tissues and organs[ 6 , 7 ]. Research has shown that CEUS can accurately visualize the microvascular perfusion of pulmonary lesions[ 8 ]. This study compared between the diagnostic efficacy puncture biopsy guided by CEUS and that by conventional ultrasound in peripheral lung lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) is widely used for ultrasound diagnosis of various tissues and organs[ 6 , 7 ]. Research has shown that CEUS can accurately visualize the microvascular perfusion of pulmonary lesions[ 8 ]. This study compared between the diagnostic efficacy puncture biopsy guided by CEUS and that by conventional ultrasound in peripheral lung lesions.…”
Section: Introductionmentioning
confidence: 99%